A CORPUS-BASED ANALYSIS OF MEDICAL VOCABULARY IN ACADEMIC JOURNALS (International journal of medical sciences, 2025)
This article presents a corpus-based analysis of medical vocabulary commonly used in contemporary academic journals. It explores the lexical, semantic, and functional characteristics of key medical terms, examines their frequency and distribution across different journal types, and identifies linguistic patterns that shape scientific communication in the medical field. The study highlights how corpus linguistics contributes to the understanding of terminology usage, variation, and conceptual development within medical discourse. Special attention is given to neologisms, specialized terminology, and multi-word expressions frequently encountered in peer-reviewed publications. The findings demonstrate the importance of corpus-based methods for improving academic writing, enhancing translation accuracy, and supporting the development of medical English teaching materials.